STUDI TENTANG KEMAMPUAN PENYESUAIAN DIRI SISWA TUNAGRAHITA DALAM MENGIKUTI PROSES PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF (STUDI PADA SISWA TUNAGRAHITA DI SDLB NEGERI SEDURI, MOJOSARI-MOJOKERTO) - DWI FITRIAWAN, RENDRA (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Education for children with special needs can be done in various ways, including through physical education. Form of an appropriate physical education program is an adaptive physical education program. In accordance with the handicap of the mental retardation children which means that the deterioration level of intelligence on children, affecting patterns of thought, mental, and social behavior on children. Students will receive coaching mental retardation children for physical education became the major task of physical education teachers. Learning program will be successful if the focus of activities aimed in improving levels of physical ability and students’ physical disability and minimize barriers achieved in life. Therefore, a physical education teacher should have a positive attitude towards them and provide motivation not to feel inferior and isolated from its environment. The purposeof this studywastodetermine the ability ofchildadjustmentfollowing the learning process Mental Retardation in adaptive physical educationat Special School (SLB) seduriAffairs, Mojosari-Mojokerto. The result of this research it can be concluded that the learning process of physical education especially for mental retardation children at MRES Seduri, Mojosari-Mojokerto using lectures, demonstrations, and assignments. If there are students who have difficulty in performing the movement because of its limitations, it is used by an individual approach to the students who have trouble in movement. As for the material being taught is not much different from normal children, but its implementation requires modification in accordance with the limitations of the students. Keywords: Adjustment, Mental Retardation, Physical Education.